2017
DOI: 10.1016/j.carbpol.2017.03.068
|View full text |Cite
|
Sign up to set email alerts
|

Rheology of Laponite-scleroglucan hydrogels

Abstract: a b s t r a c tBoth Laponite and scleroglucan can find several applications in various fields (from industrial to biomedical one) in virtue of their peculiar features and rheological properties displayed in aqueous phases. Structural states of Laponite dispersions strongly depend on concentration and ionic strength. When attractive and repulsive interparticle interactions are so effective that they lead to arrested states (attractive gel or repulsive glass), the rheological behavior of the dispersion undergoes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 58 publications
3
34
0
1
Order By: Relevance
“…Based on the results of dynamic oscillatory shear test, it was indicated that Laponite, especially above 5 wt.% content, improved the rheological characteristics performance, attributed to the polymer-particle bridging interaction via the formation of Van der Waals forces, ionic and hydrogen bonds (between the hydrogen and hydroxyl of clay and those of the groups Dglucoronic, D-mannose of the SSG chains), and electrostatic attractions (between anionic groups of SSG molecules and positively charged edges of nanoclay platelets) as already mentioned in literature (Dávila & d'Ávila, 2017;Lapasin et al, 2017;Zlopasa, Norder, Koenders, & Picken, 2016). When nanoparticle concentrations increased, the number and size of agglomerated (soft flocks) and aggregated (hard clusters) SSG-Laponite increased and bridging interaction was strengthened.…”
Section: Frequency Sweepsupporting
confidence: 52%
See 1 more Smart Citation
“…Based on the results of dynamic oscillatory shear test, it was indicated that Laponite, especially above 5 wt.% content, improved the rheological characteristics performance, attributed to the polymer-particle bridging interaction via the formation of Van der Waals forces, ionic and hydrogen bonds (between the hydrogen and hydroxyl of clay and those of the groups Dglucoronic, D-mannose of the SSG chains), and electrostatic attractions (between anionic groups of SSG molecules and positively charged edges of nanoclay platelets) as already mentioned in literature (Dávila & d'Ávila, 2017;Lapasin et al, 2017;Zlopasa, Norder, Koenders, & Picken, 2016). When nanoparticle concentrations increased, the number and size of agglomerated (soft flocks) and aggregated (hard clusters) SSG-Laponite increased and bridging interaction was strengthened.…”
Section: Frequency Sweepsupporting
confidence: 52%
“…Just recently, rheological characterization of alginate-Laponite and scleroglucan-Laponite hydrogels has been carried out to assay the reinforcing effects of Laponite, in particular to analysis the physical gelation due to the electrostatic interactions between the anionic groups of alginate and scleroglucan chains and positively charged rim of Laponite disks (Dávila & d'Ávila, 2017;Lapasin, Abrami, Grassi, Sebenik, & Šebenik, 2017). Although a lot of facts on…”
mentioning
confidence: 99%
“…23 To date, understanding the structural dynamics and aging, 2427 as well as the rheological properties of Laponite-based systems have been the focus of research. 26,2833 Depending on the pH, H + or OH − may dissociate from the nanoclay edge. 33 Dissociation of H + from the edge occurs beyond the point of zero charge pH (isoelectric point, pH ~ 11 for Mg-OH), 34 resulting in completely negatively charged particles.…”
Section: Introductionmentioning
confidence: 99%
“…Pode ocorrer periodicamente a substituição dos átomos de magnésio por átomos de lítio (Li), causando uma deficiência de íons positivos que é contraposta pela presença de cátions de sódio (Na + ) presentes nos espaços interplanares. 16 Em recorrência das diferentes propriedades dos hidrogéis citadas anteriormente, os mesmos possuem diversas aplicações, como lentes de contato, 17 tecidos artificiais, 18 sensores e atuadores, 19 tratamentos de câncer, 20 substituição de cartilagens, tratamento de queimaduras, liberação controlada de fármacos, liberação controlada de pesticidas, entre outras. 21,22 Artigo curtos e posteriormente liberar essa água de maneira mais lenta e controlada, agrega-se aos hidrogéis a possibilidade de carregar diversos componentes presentes em soluções aquosas.…”
Section: Introductionunclassified